Absence of protective effect of oral contraceptive use on the development of rheumatoid arthritis: a meta‐analysis of observational studies. (8th September 2014) - Chen, Qi; Jin, Zhichao; Xiang, Chun; Cai, Qing; Shi, Wentao; He, Jia
Abstract Aim To investigate the association between oral contraceptive (OC) use and development of rheumatoid arthritis (RA). Method We conducted a systematic review and meta‐analysis based on observational studies. Summary estimates were obtained using fixed‐ or random‐effects models as appropriate. Dose‐response meta‐analysis, subgroup analysis, cumulative meta‐analysis, sensitivity analysis and publication bias tests were performed. Results Our meta‐analysis of 28 studies included 18 case‐control, three nested case‐control, and seven cohort studies. In case‐control studies, the risk of RA of ever, current and past OC users was 0.69 (95% confidence interval [CI], 0.53–0.89), 0.71 (95% CI, 0.48–1.06) and 0.67 (95% CI, 0.44–1.01), respectively, compared to that of never OC users. In prospective studies, the corresponding odds ratios (ORs) of ever, current and past OC use were 1.00 (95% CI, 0.87–1.15), 0.93 (95% CI, 0.70–1.23) and 0.93 (95% CI, 0.78–1.12), respectively. A cumulative meta‐analysis showed that the pooled ORs moved to the midline with an increase in sample size as years passed. There was an inverse association between OC use and severity of RA (OR, 0.41; 95% CI, 0.22–0.78). Dose‐response meta‐analysis of the study data revealed that the association between OC use and risk of RA was independent of duration of OC use. Conclusion OC use has no protective effect on RA onset, but appears to prevent progression to severe RA. In addition, OC use has a lower protective effect on the risk of RA with change in OC composition. Finally, no cumulative effect was found between OC use and risk of RA.